The Existence of Arbitration as an Alternative to Business Dispute Resolution: Between Procedural Efficiency and Enforcement Challenges - Sandra Ayu Wandira; Fauzan Habibi Lubis; Jakaria; Rabiatul Adawiyah Nasution; Nadzri Adlani Nasution (ISNU Sumatera Utara, 2024)
The development of modern business activities that are increasingly complex has increased the potential for disputes between parties, both in national and international business relations. The dispute resolution mechanism through litigation is often considered not to be fully able to meet the needs of the business world because the procedure is formal, takes a relatively long time, and lacks flexibility for the parties. These conditions encourage arbitration to develop as an alternative dispute resolution that offers a more adaptive mechanism through the principles of autonomy of the parties, confidentiality, and legal certainty. This study aims to analyze the position of arbitration as an alternative to dispute resolution in the context of business law, especially regarding its characteristics, underlying legal principles, and effectiveness in providing dispute resolution for business actors. This study uses normative legal research methods with statute approaches and conceptual approaches, through the study of primary, secondary, and tertiary legal materials that are analyzed juridically qualitatively. The results of the study show that arbitration has a strategic position in resolving business disputes because it provides procedural flexibility, expertise-based settlement, confidentiality protection, and final and binding awards. However, the effectiveness of arbitration still faces challenges related to the implementation of awards, the professionalism of arbitrators, and harmonization with the national judicial system. Thus, arbitration serves not only as an alternative to litigation, but also as a legal instrument that supports legal certainty, efficiency, and stability of modern business relationships.